Geographical Distribution of Irrigation and Drainage Projects in the Study Area - Ahmed, Ismael Mohamed; Al-Hasnawi, Zainab Wanass (Al-Adab Journal, 2022)
Study for a high study rate to get a clear study to get a clear study to get a study percentage in Earth’s gravity. It is restricted to the colder months of the year, and therefore irrigated agriculture depends on surface water in the first place, and on this basis this topic was chosen to contribute to giving a study on the possibility of achieving the optimal use of water resources and promoting them in order to preserve the soil, and it was found that there is a relationship between Natural and human geographical factors in determining soil characteristics, water needs, and irrigation methods by which irrigation needs are transferred to agricultural crops, and through this, the extent of their impact on soil properties is known.